2012
DOI: 10.1007/s00784-012-0810-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of open mouth and rubber dam on upper airway patency and breathing

Abstract: Breathing pattern may become deteriorated by airway obstruction during dental treatments requiring a rubber dam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 10 publications
2
13
0
Order By: Relevance
“…27,28 The main reasons for the negative opinion of GDPs towards RD application are difficult placement, time required for application, occasional patient complaints and cost. 8,10,15,29 In an attempt to overcome these drawbacks, other isolation techniques have been undertaken by GDPs during root canal treatment. In addition to cotton rolls and/or gauze, some authors and GDPs claimed that other isolation techniques such as Isolite (Benbrook Dental, USA) are able to enhance visibility, reduce the risk of damage of porcelain surfaces, minimize the risk of perforation and can be useful in young patients with incompletely erupted teeth.…”
Section: Factors Affecting Rubber Dam Use After Graduationmentioning
confidence: 99%
“…27,28 The main reasons for the negative opinion of GDPs towards RD application are difficult placement, time required for application, occasional patient complaints and cost. 8,10,15,29 In an attempt to overcome these drawbacks, other isolation techniques have been undertaken by GDPs during root canal treatment. In addition to cotton rolls and/or gauze, some authors and GDPs claimed that other isolation techniques such as Isolite (Benbrook Dental, USA) are able to enhance visibility, reduce the risk of damage of porcelain surfaces, minimize the risk of perforation and can be useful in young patients with incompletely erupted teeth.…”
Section: Factors Affecting Rubber Dam Use After Graduationmentioning
confidence: 99%
“…7,8 It is important to understand what the jaw open position does to the patient's airway so that treatment can be adapted to the patient's needs. Some patients may need more breaks during treatment to keep their oxygen saturation higher.…”
mentioning
confidence: 99%
“…It has been reported that head and jaw positions would significantly affect the airway dimensions. 8 However, comparing open jaw position to closed jaw position and its influence on the airway dimensions using 3D CBCT imaging has not been previously studied.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Rubber dam isolation was not done in the present case, which might be considered as a major limitation, but adequate care was maintained to prevent contamination of the operating field using cotton rolls and high volume saliva evacuators. Though, rubber dams increase the quality and safety of dental treatments, open mouth position plays the largest role in decreased upper airway patency, and open mouth position with a rubber dam may further disrupt breathing pattern, as stated by Iwatani et al [11]. Since the patient revealed a habit of mouth breathing, in addition to the fact, that there was a discomfort caused due to airway obstruction, rubber dam application was terminated in the current case.…”
Section: Discussionmentioning
confidence: 73%